This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: and substitute into either equation (2) or (3) to find y . Substitute z = 3 into equation (1). Substitute x = 4 and z = 3 into equation (2). Use the original equations to check the solution (the check is left to you). The solution is x = 4, y = –2, z = 3....
View Full Document
This note was uploaded on 11/10/2011 for the course MATH 1310 taught by Professor Staff during the Fall '07 term at Texas State.
- Fall '07